Productivity and soil fertility as influenced by intercropping row ratios and nutrient management under aonla (Emblica officin alis) based hortipasture system in semi-arid conditions of Rajasthan - Meena, L.R.; Mann, J.S.; Meena, Ramkesh (Indian Journal of Agroforestry, 2020)
An experiment was conducted during the kharif seasons of 2006 and 2007 on sandy-loam soil to study the response of different row ratios of cowpea (Vigna unguiculata) and Cenchrus (Cenchrus setigerus) with different nutrient management on productivity and build up of soil fertility under 5 year old Aonla plantation in farmers field. Row ratio of 2: 1 in cow pea and Cenchrus resulted in significantly higher dry fodder yield (3.34 t ha-1). However, seed production in Cenchrus was the highest in case of 1: 2 row ratio (140.55 kg ha-1) followed by 1:1 and 2:1 row ratios. Fruit yield of aonla was recorded maximum under storey (6.38 t ha-1) growing of legume and grass in 2: 1 row ratio than 1: 1 and 1: 2 row ratios. The maximum organic carbon content, available N and P were improved when legume and grass grown in 2: 1 row ratio to the tune of 42.54, 37.64 and 69.17% higher than initial soil content of these nutrients. Application of N and P @40 kg N ha-1 + 60 kg P2O5 ha-1 + bacterial inoculation (Azospirillum brasilense and Pseudomonas striata) had improved in mean dry fodder yield (122.81%) over control treatment. Among the fertility treatments, seed yield of Cenchrus was increased by 20.99% higher at 40 kg N ha-1 + 60 kg P2P5 ha-1 + bacterial inoculation over no fertilization (control). Similarly, the maximum yield (7.01 t ha-1) of aonla fruit was noticed with the application of 40 kg N ha-1 and 60 kg P2O5 ha-1 in conjunction with bacterial inoculation. At the end of 2 years experimentation on the same site, physico-chemical properties like bulk density and soil pH recorded perceptible decrease from initial values, while soil organic carbon content, available N and P exhibited marked improvement over initial values.